(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Varicose veins are a common manifestation of chronic venous disease and result from valvular incompetence and venous reflux, leading to pain, heaviness, edema, skin changes, and reduced quality of life. Endovenous laser ablation has emerged as a minimally invasive alternative to conventional surgery because it offers less postoperative morbidity, shorter recovery, and better patient acceptance. The 1470 nm diode laser, with greater absorption by water in the vein wall, is expected to produce more effective and uniform ablation with fewer complications. Aim & Objective: To assess the one-year efficacy of 1470 nm endovenous diode laser ablation in patients with varicose veins using duplex ultrasound, and to evaluate symptom improvement, recurrence, procedural parameters, post-treatment complications, and patient-reported outcomes. Materials & Methods: This prospective observational study was conducted at G.R. Medical College and J.A. Group of Hospitals, Gwalior, from April 2024 to September 2025 in 94 adults with primary symptomatic varicose veins (CEAP C2 to C6). All underwent 1470 nm endovenous diode laser ablation and completed a one-year follow-up for assessment of clinical profile, duplex findings, procedural details, complications, recurrence, and Venous Clinical Severity Score. Results: Complete occlusion at 12 months was achieved in 94.68% cases, while recurrence occurred in 5.3%. Radial fiber showed significantly lower recurrence than bare fiber (p = 0.012). Mean VCSS improved from 8.11 ± 3.02 before treatment to 2.55 ± 3.17 in 12 months (p < 0.001). Complications were minor and included ecchymosis, transient paresthesia, and thrombophlebitis. Conclusion: 1470 nm endovenous diode laser ablation is a safe, effective, and minimally invasive treatment for varicose veins with excellent one-year outcomes.